Layered inorganic-organic clay-like nanocomposites rearrange to form silsesquioxanes on acid treatment - Kumaraswamy, Guruswamy; Deshmukh, Yogesh S.; Agrawal, Vikrant V.; Rajmohanan, P. (Journal Physical Chemistry B, 2005)
The formation of talc-like compounds by the condensation of organotrialkoxy silanes with magnesium hydroxide has been recently reported. These represent layered hybrid nanomaterials that have a layer thickness of around 1 nm, have organic moieties covalently linked to the layer surfaces, and are called ``organoclays.'' We show that such compounds are sensitive to acid treatment. When a phenylclay is treated with hydrochloric acid, magnesium leaches out, destroying the layered structure. The extent to which magnesium is leached out is a function of the time of the acid treatment and the concentration of the acid used. Magnesium leaches out rapidly when the concentration of acid used to treat the phenyl-clay is higher, and the extent of structural magnesium that is leached out is also higher for higher acid concentrations. Removal of the magnesium rearranges the structure of the phenyl-clay to form oligomeric phenylsilsesquioxanes. FTIR and NMR suggest that the silsesquioxanes formed by acid treatment of the phenyl-clay comprise a mixture of ladderlike and cagelike structures.

Lamellar melting, not crystal motion, results in softening of polyoxymethylene on heating - Kumaraswamy, Guruswamy; Surve, Nikita S.; Mathew, Renny; Rana, Abhimanyu; Jha, Saroj K.; Bulakh, Neelima N.; Nisal, Anuya; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Ratnagiri, Ram (Macromolecules, 2012)
We probe temperature-dependent changes in the semicrystalline microstructure of polyoxymethylene using a combination of modulated DSC, SAXS, and solid-state NMR to characterize macroscopic behavior, lamellar-level structure, and molecular environments, respectively, and correlate these with the change in mechanical properties probed using DMA and AFM. Two model samples are investigated: a melt crystallized sample prepared by injection molding and a sample obtained by crystallization from dilute solution. Our investigations reveal that, for both samples, there is an increase in crystalline motions and in the amorphous content on heating. DMA and AFM measurements reveal that the modulus of the molded sample decreases on heating to about 100 degrees C; however, there is a significant difference in behavior of the solution crystals, where we observe no significant decrease in stiffness (from AFM measurements). Thus, in contrast to previous reports, we demonstrate that the decrease in modulus on heating polyoxymethylene does not correlate with chain motions in the crystalline regions. We use SAXS to probe the semicrystalline morphology for the samples on heating and show that, for the molded sample, there is a distribution of lamellar thickness at room temperature and that the thin lamellae in this distribution melt on heating. In contrast to the behavior of the melt crystallized samples, the solution crystals exhibit no change in the lamellar stacking on heating to 150 degrees C. We also demonstrate that, on heating, the amorphous regions in the solution crystals always appear to have restricted mobility while there are mobile and low mobility amorphous regions in the molded samples. Our results suggest that, contrary to conventional belief, the decrease in modulus on heating polyoxymethylene arises not from motions in the crystalline lamellae but primarily from melting of thin lamellae.

Large centimeter-sized macroporous ferritin gels as versatile nanoreactors - Kumari, Sushma; Kulkarni, Amol; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Chemistry of Materials, 2013)
Organized assemblies of bionanoparticles such as ferritin provides templates that can be exploited for nanotechnological applications. Organization of ferritin into well-defined three-dimensional assemblies is challenging and has attracted considerable attention recently. We have synthesized, for the first time, large (centimeter-sized) self-standing macroporous scaffold monoliths from ferritin bionanoparticles, using dynamic templating of surfactant H-1 domains. These scaffolds comprise three-dimensionally connected strands of ferritin, organized as a porous gel with porosity similar to 55 mu m. The iron oxide inside the ferritin scaffold can be easily replaced with catalytically active monodisperse zerovalent transition metal nanoparticles using a very simple protocol. Since the ferritin is cross-linked in the scaffold, it is significantly robust with enhanced thermal stability and better tolerance toward several organic solvents in Comparison to the native ferritin bionanoparticle. In addition, the scaffold macropores facilitate substrate and reagent transport and hence the monoliths containing active Pd or iron oxide nanoparticles inside apo-ferritin bionanoparticles were used as a recyclable heterogeneous catalyst for the oxidation of 2,3,6-trimethyl phenol to 2,3,6-trimethyl-1,4-benzoquinone (precursor for Vitamin E synthesis) and for Suzuki-Miyaura cross-coupling reaction in both aqueous and organic solvents. The protein shell around the nanoparticles protects them from agglomeration, a phenomenon that otherwise plagues nanoparticles-based catalysis. The presence of macropores allow the ferritin scaffold to act as catalytic monolith for continuous flow reactions having rapid reaction rates, while offering a low pressure drop. Finally, the Pd@apo-ferritin scaffold was immobilized inside a steel cartridge and used for the continuous flow hydrogenation of alkenes to their corresponding alkanes for 15 cycles without any loss of activity.
Keywords: catalysis; continuous flow; ferritin; gel; macroporous materials; Self-assembly

Large amplitude oscillatory shear induces crystal chain orientation in velocity gradient direction - Sreenivas, K.; Kumaraswamy, Guruswamy (ACS Macro Letters, 2014)
Imposition of large amplitude oscillatory shear (LAOS) on crystallizing polymer melts results in lamellar orientation in the shear gradient direction, in contrast to the flow-orientation observed for steady shear. LAOS enhances the formation of plate-like nuclei and orients their normals in the gradient direction. An Arrhenius temperature dependence (with activation energy approximate to 226 kJ/mol) characterizes the relaxation of crystal orientation with annealing.

Linking catalyst-coated isotropic colloids into ``active'' flexible chains enhances their diffusivity - Biswas, Bipul; Manna, Raj Kumar; Laskar, Abhrajit; Kumar, P. B. Sunil; Adhikari, Ronojoy; Kumaraswamy, Guruswamy (ACS Nano, 2017)
Active colloids are not constrained by equilibrium: ballistic propulsion, superdiffusive behavior, or enhanced diffusivities have been reported for active Janus particles. At high concentrations, interactions between active colloids give rise to complex emergent behavior. Their collective dynamics result in the formation of several hundred particle-strong flocks or swarms. Here, we demonstrate significant diffusivity enhancement for colloidal objects that neither have a Janus architecture nor are at high concentrations. We employ uniformly catalyst-coated, viz. chemo-mechanically, isotropic colloids and link them into a chain to enforce proximity. Activity arises from hydrodynamic interactions between enchained colloidal beads due to reaction-induced phoretic flows catalyzed by platinum nanoparticles on the colloid surface. This results in diffusivity enhancements of up to 60% for individual chains in dilute solution. Chains with increasing flexibility exhibit higher diffusivities. Simulations accounting for hydrodynamic interactions between enchained colloids due to active phoretic flows accurately capture the experimental diffusivity. These simulations reveal that the enhancement in diffusivity can be attributed to the interplay between chain conformational fluctuations and activity. Our results show that activity can be used to systematically modulate the mobility of soft slender bodies.
Keywords: active matter; Brownian motion; colloidal assembly; diffusivity; ice templating

Living in the polymer age - Kumaraswamy, Guruswamy (Resonance, 2017)

Large PAMAM dendron induces formation of unusual P4332 mesophase in monoolein/water system - Kumar, Manoj; Patil, Naganath Ganapatarao; Ambade, Ashootosh V.; Kumaraswamy, Guruswamy (Langmuir, 2018)
Compact macromolecular dendrons have been shown to induce the formation of discontinuous inverse micellar assemblies with Fd3m symmetry in monoolein/water systems. Here, we demonstrate that a large PAMAM dendron (G5: fifth generation) induces the formation a very unusual mesophase with P4332 symmetry. This mesophase had previously been observed in monoolein/water systems only on addition of cytochrome C. The P4332 mesophase can be considered an intermediate phase between the bicontinuous Ia3d and discontinuous micellar mesophases. In this unusual phase, every third rod junction of the Ia3d mesophase is replaced with a spherical micelle. We present a detailed investigation of the phase behaviour of monoolein/water as a function of G5 concentration and temperature. Addition of 1% G5 in 85/15 monoolein/water system induces a transition from the L to Ia3d phase. Further increase in G5 concentration to above 2% induces the formation of the P4332 phase. Thus, incorporation of G5 yields a qualitatively different phase diagram when compared with incorporation of lower generation PAMAM dendrons (G2 – G4) in monoolein/water, where the reverse micellar Fd3m phase forms. PAMAM dendrons of all generations, G2 – G5, bear terminal amine groups that interact with the monoolein head group. The compact molecular architecture of the dendrons and these attractive interactions induce bending of the monoolein bilayer structure. For smaller dendrons, G2 – G4, this results in the formation of the Fd3m phase. However, the large size of the G5 dendron precludes this and a rare intermediate phase between the Ia3d and discontinuous micellar phase, the P4332 mesophase forms instead.